2019
DOI: 10.1111/ics.12565
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and topical delivery of phenylethyl resorcinol

Abstract: Objective Phenylethyl resorcinol (PR) has been used widely in the personal care industry as a novel skin lightening ingredient. Surprisingly, there is only limited information describing the physicochemical properties of this active. Therefore, the primary objective of this study was to perform a comprehensive characterization of PR. A secondary objective was to investigate the delivery of this molecule to mammalian skin. Methods Phenylethyl resorcinol was characterized using differential scanning calorimetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…No evaporation was evident for the GLY and 1-5P formulations. These findings are consistent with previous reports on the evaporation of neat GLY, DMI, PG and TC(Haque et al, 2017b;Zhang et al, 2019b). To our knowledge DVS has not been used previously to characterise the behaviour of NIA solutions under controlled conditions of temperature and humidity.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…No evaporation was evident for the GLY and 1-5P formulations. These findings are consistent with previous reports on the evaporation of neat GLY, DMI, PG and TC(Haque et al, 2017b;Zhang et al, 2019b). To our knowledge DVS has not been used previously to characterise the behaviour of NIA solutions under controlled conditions of temperature and humidity.…”
supporting
confidence: 93%
“…Even though the mechanism by which TC interacts with the skin is not known, its potential to act as a penetration enhancer has been reported for a number of compounds (Lane, 2013). Puglia and Bonina (2008) PG is a hydrophilic solvent that has been used in topical formulations as a solvent for many actives (Lane, 2013;Haque et al, 2017b;Haque et al, 2018;Paz-Alvarez et al, 2018;Hossain et al, 2019;Iliopoulos et al, 2019;Zhang et al, 2019b). In the present work, 5 μL doses of 3 % (w/w) NIA in PG were applied to porcine skin and the percentage permeation after 24 h was 19.2 %.…”
Section: Permeation Studies Using Neat Solventsmentioning
confidence: 99%
“…This means good agreement, as shown by Table 2. Zhang and co-workers [23] have recently reported PER solubility data in propylene glycol (PG), glycerol and dimethylisosorbide (DMI). The reported values for PG are in good agreement with the results found in this study, but the data for DMI and glycerol are significantly different, which may be explained by the differences in their method, in the amount of solid excess or in the crystal form.…”
Section: Solubility Of Per In Different Solventsmentioning
confidence: 99%
“…It has suitable UV properties and reasonable solubility in the solvents examined, which made it a good model for the study. A recently published study from Zhang and co-workers [23] has reported a comprehensive characterisation of PER, including HPLC-based logP and solubility and in vitro permeation studies through human and porcine skin. The permeation profile of PER was investigated in finite dose conditions using Franz diffusion cell method and applying PER in three different vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Total mass recovery of RSV was checked by considering the mass balance of RSV distributed among the skin, and the donor and receptor compartments [7,28]. At the end of the assay, the Franz diffusion cells were disassembled, and the residual Pickering emulsion (or control sample) in the donor compartment was diluted with 30 ml of fresh receptor fluid solution.…”
Section: Resveratrol Encapsulation Efficiencymentioning
confidence: 99%